ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL-SOAL PADA MATERI BANGUN RUANG SISI DATAR (BRSD) - Dikdik Adi Putra; Risma Amelia; Nelly Fitriani (IKIP Siliwangi, 2022)
This study aims to analyze the students' difficulties in solving problems on the flat side of the space. The method used in this study is a qualitative descriptive method with the population used is 26 junior high school students in one of the schools in Cianjur Regency. The data collection technique carried out in this qualitative descriptive study was carried out by giving a description test question of 5 questions. The data analysis technique used is data reduction, data presentation and concluding research results. The conclusion of the data is taken from the percentage of the question indicators and then concludes the average results of the overall indicators. The result of this research is that students are still wrong in solving flat-sided space problems, precisely on questions number 4 and 5, with the indicator for question no 4 is determining the volume of cubes and blocks and question number 5 with indicators determining the surface area of the pyramid. The difficulty of students in solving questions number 4 and 5 is that students do not understand the problems contained in the questions so that students are wrong about taking steps in solving problems. In addition, students' errors in solving flat-sided geometrical problems are (1) negligence in analyzing the problem; (2) Lack of students' accuracy in answering questions; (3) It is difficult to determine how to answer the question.